Evaluation of velopharyngeal function using high-speed cine-magnetic resonance imaging based on T2-weighted sequences: a preliminary study. Issue 4 (April 2020) - Joujima, T.; Oda, M.; Sasaguri, M.; Habu, M.; Kataoka, S.; Miyamura, Y.; Wakasugi-Sato, N.; Matsumoto-Takeda, S.; Takahashi, O.; Kokuryo, S.; Sago, T.; Yoshiga, D.; et al.
Abstract: The objective was to introduce a new technique for visualizing the three-dimensional (3D) movements of velopharyngeal-related muscles using high-speed cine-magnetic resonance imaging (MRI) based on T2-weighted sequences. The evaluation of phonation- and water swallowing-related events was performed in 11 healthy subjects. Specifically, whether cine-MRI could precisely visualize normal velopharyngeal function during these two events was examined. The 3D movements of the soft palate, superior pharyngeal constrictor muscles, and levator veli palatini muscles were visualized in all 11 subjects. A noteworthy finding was that the magnetic resonance signals of the superior constrictor pharyngeal muscles and the levator veli palatini muscles were significantly higher during phonation and during water swallowing than at rest. This initial study suggests that the 3D movements of velopharyngeal-related muscles can be successfully and precisely visualized without side effects. The magnetic resonance signal changes seen in the superior pharyngeal constrictor and levator veli palatini muscles using the technique described here should be useful to develop better methods of evaluation of velopharyngeal function.